2023
DOI: 10.1099/jgv.0.001835
|View full text |Cite
|
Sign up to set email alerts
|

An oseltamivir-resistant avian H1N1 influenza A virus can transmit from mallards to chickens similarly to a wild-type strain: implications for the risk of resistance transmission to humans

Abstract: The neuraminidase inhibitor (NAI) oseltamivir is stockpiled globally as part of influenza pandemic preparedness. However, oseltamivir carboxylate (OC) resistance develops in avian influenza virus (AIV) infecting mallards exposed to environmental-like OC concentrations, suggesting that environmental resistance is a real concern. Herein we used an in vivo model to investigate if avian influenza H1N1 with the OC-resistant mutation NA-H274Y (51833/H274Y) as compared to the wild-type (wt) strain (51833 /wt) could t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…However, other evidence has suggested that resistance in the environment may be affected by human medicines. For example, recent evidence suggests that use of oseltamivir in humans may result in environmental exposure for birds that in turn develop oseltamivir-resistant avian influenza virus (44).…”
Section: Human-animalmentioning
confidence: 99%
“…However, other evidence has suggested that resistance in the environment may be affected by human medicines. For example, recent evidence suggests that use of oseltamivir in humans may result in environmental exposure for birds that in turn develop oseltamivir-resistant avian influenza virus (44).…”
Section: Human-animalmentioning
confidence: 99%
“…Fortunately, the administration of oseltamivir as prophylaxis in poultry flocks is costly, which renders its wide application difficult; nevertheless, oseltamivir-resistant H5N1 AIVs have been also reported [87][88][89][90]. Experimentally, several studies revealed the development of oseltamivir-resistant mutants in aquatic birds (mallards) after exposure to oseltamivir treatment and the ability of these mutants to transmit to domestic chickens [91,92]. Although oseltamivir-resistant IAVs are documented in humans [93,94], the drug is still effective and is considered the drug of choice in treating human influenza infections.…”
Section: Improper Antiviral Drug Prescription To Control Aivs In Avia...mentioning
confidence: 99%
“…Finally, it has been demonstrated that mallards can transmit an avian influenza virus that is oseltamivir-resistant to chickens. As this mutant is able to cross the species barrier and also maintain fitness, it could be able to infect humans [ 21 ]. Finding alternative antiviral drugs with distinct modes of action is therefore urgently needed to fight infection by emerging viruses with pandemic potential, especially those carrying drug resistance markers.…”
Section: Introductionmentioning
confidence: 99%